Perancangan Fixture Proses Gurdi untuk Produksi Komponen Brake Pads - Suci Rahmawati; Vivi Triyolanda; Neta Harimeni; Meutia Syarah (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2010)
Brake pads is used to stop the rapid of vehicle while braking process is done. In making process if brake pads is needed a tool to make a operator work easier and can produce the brake pads component more precision, especially in making a hole process. A tool which is designed in drilling process in production of brake pads component use locator 3-2-1 principt in a placement the locator, using clamping to grip the component, and construction of jig dan fixture that is designed must be suitable with needs of making a hole process this brake pads component. To produce this tool, the cost must be calculated, such as direct cost, indirect cost and fixed cost to cover the 1200 lot sizes of this brake pads component. Based on design of this tool, it can be concluded that a tool which design of the drilling process can give benefit because it can help the operator in their work and it can produce the brake pads component more precision, and the rejected product can be minimized presisi. In addition, the set up time can be decreased and the cost be reduced.